'I can succeed at this': engagement in service learning in schools enhances university students' self-efficacy. Issue 12 (2nd December 2022) - Gutzweiler, Raphael; Pfeiffer, Simone; In-Albon, Tina
ABSTRACT: Engaging in service learning has been linked to multiple positive outcomes in students, such as an increase in self-efficacy. Effects have been found on both general and domain-specific self-efficacy. Research on service learning has indicated that feedback and gender had an impact on the increase in self-efficacy, though findings are mixed. The present study aimed to determine how service learning experiences at a university can be optimally designed to boost college students' self-efficacy, while examining the effects of feedback and gender on general and teaching self-efficacy. Over 2 years, 267 bachelor's students in psychology ( M age  = 23.08 years, SD  = 3.61; 80.5% female) conducted modularized prevention programs in the context of mental health at primary and secondary schools. Students rated their general and teaching self-efficacy before (T1), during (T2), and after (T3) conducting the program. The results indicate a positive effect of engaging in service learning on students' general ( d  = 0.30) and teaching ( d  = 0.68) self-efficacy from T1 to T3 with significant increases only in female students, and after receiving feedback. Engaging in service learning reduced gender-specific differences in self-efficacy. Feedback increased general and teaching self-efficacy. Female students seemed to benefit more than male students.